86. Use of a Novel Clinical Decision Support Tool for Pharmacist-Led Antimicrobial Stewardship in Patients with Normal Procalcitonin. (31st December 2020) - Watkins, Andrew B; Van Schooneveld, Trevor C; Reha, Craig; Anderson, Jayme; McGinnis, Kelley; Bergman, Scott
Abstract: Background: Our Antimicrobial Stewardship Program (ASP) instituted review of patients on antibiotics with procalcitonin (PCT) < 0.25 mcg/L in 2012. In 2018, a clinical decision support (CDS) tool was implemented as part of a "daily checklist" for frontline pharmacists to assist in this patient review. We sought to validate the effectiveness of this tool for pharmacist-led PCT-based antibiotic stewardship. Methods: A retrospective cohort design was used to assess antibiotic de-escalation after PCT alert in patients on antibiotics for lower respiratory tract infections (LRTI). Secondary outcomes included antibiotic use and length of stay (LOS) in patients with PCT interventions vs those without. Results: From 1/2019 to 11/2019, 652 of 976 (66.8%) PCT alerts were addressed by pharmacists. Of these, 331 were in patients with a respiratory-related diagnosis at discharge and 165 alerts were in patients on antibiotics specifically for LRTI over 119 encounters. Pharmacists made or attempted interventions after 34 (20.6%) of these alerts, with narrowing spectrum or converting to oral therapy being the most common interventions. Antibiotics were completely stopped in 4 of these interventions (11.8%). Patients with pharmacist intervention had 125 fewer antibiotic days of therapy (DOT) in the hospital, and changes were made to an additional 56 DOT (narrower therapy, IV to PO, dose optimization) following the alert. Two cases (5.9%) subsequently had therapy escalated within 48 hours. Vancomycin was the most commonly discontinued antibiotic with an 85.3% use reduction in patients with interventions compared to 27.4% discontinuation in patients with no documented intervention (p=0.0156). Alerts eligible for de-escalation but with no pharmacist intervention represented 140 DOT. LOS was similar in patients from both groups (median 6.4 days vs. 7 days, p=0.81). Conclusion: Interventions driven by a CDS tool for pharmacist-driven antimicrobial stewardship in patients with normal PCT resulted in fewer DOT and significantly higher rates of vancomycin discontinuation. Additional interventions could have potentially prevented 140 DOT. We feel refinement of this tool can lead to more meaningful CDS, reduce alert fatigue, and likely increase intervention rates. Disclosures: All Authors : No reported disclosures